3D Multi‐Agent Formation Control with Rigid Body Maneuvers. Issue 3 (20th May 2018) - Zhang, Pengpeng; de Queiroz, Marcio
Abstract: In this paper, we propose a control scheme for the formation maneuvering problem of multi‐agent systems where the team of agents can translate and rotate as a virtual rigid body in 3D. Using the single‐integrator model, we formulate the basic control law which is comprised of a formation acquisition term, function of the graph rigidity matrix, and a rigid body maneuvering term. The control is dependent on the relative position of agents that are connected in an infinitesimally and minimally rigid framework in addition to the desired rigid body motion of the formation. To facilitate the design of the rigid body maneuver, one agent in the convex hull of the formation serves as the reference point for the rotation component. A simulation study demonstrates the formation controller.